What Does Society Owe Political Cartoonists?. (2nd January 2017) - Mackay, Jenn Burleson
Abstract : Political cartoonists challenge the government, question societal norms, and contribute to public discussion. They may show the public instances of injustice and help society to understand our own roles and responsibilities within the community. Yet, cartoonists are facing significant challenges in modern society. As the newspaper industry has struggled financially, fewer news organizations have continued to maintain a staff cartoonist. The shootings at France's satirical newspaper Charlie Hebdo served as a reminder of the dangers that cartoonists can face if they publish controversial cartoons. Through applications of John Rawls' political liberalism and communitarianism, this paper examines what cartoonists contribute to societal justice and their role in the community. It argues that society owes cartoonists the liberties that they need to continue upholding justice, but that cartoonists have responsibilities to the community.